PENDEKATAN INTERVENSI MIKRO SEBAGAI UPAYA REHABILITASI DAN PEMBERDAYAAN PPKS PEREMPUAN: STUDI KASUS DI RUMAH PERLINDUNGAN SOSIAL MEDAN (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Homeless and Beggars (Gepeng) are part of the Beneficiaries of Social Welfare Services (PPKS) who require special attention from both the government and society. In the city of Medan, the issue of Gepeng has become a significant social concern. Data from the Medan City Social Service in 2023 recorded 538 Gepeng individuals whose basic needs have been met, reflecting the government’s efforts in addressing this problem (dinsos.medan.go.id). This study aims to empower PPKS, particularly women, through an approach focused on skill development and motivation enhancement. The research employed a qualitative method, using observation and interviews with female Gepeng in Medan. Through Field Work Practice (PKL), the researcher was directly involved in empowerment activities. The results indicate that this approach has provided new hope for the Gepeng to initiate independent businesses, such as mobile data services, cooking, and handicrafts. This empowerment not only improved their skills but also strengthened their self-confidence and economic independence. Thus, this study contributes to reducing the number of Gepeng in Medan and enhancing their social welfare.